MELD as a metric for survival benefit of liver transplantation. Issue 5 (19th February 2018) - Luo, Xun; Leanza, Joseph; Massie, Allan B.; Garonzik‐Wang, Jacqueline M.; Haugen, Christine E.; Gentry, Sommer E.; Ottmann, Shane E.; Segev, Dorry L.
Abstract : Currently, there is debate among the liver transplant community regarding the most appropriate mechanism for organ allocation: urgency‐based (MELD) versus utility‐based (survival benefit). We hypothesize that MELD and survival benefit are closely associated, and therefore, our current MELD‐based allocation already reflects utility‐based allocation. We used generalized gamma parametric models to quantify survival benefit of LT across MELD categories among 74 196 adult liver‐only active candidates between 2006 and 2016 in the United States. We calculated time ratios (TR) of relative life expectancy with transplantation versus without and calculated expected life years gained after LT. LT extended life expectancy (TR > 1) for patients with MELD > 10. The highest MELD was associated with the longest relative life expectancy (TR =1.05 1.201.37 for MELD 11‐15, 2.29 2.492.70 for MELD 16‐20, 5.30 5.726.16 for MELD 21‐25, 15.12 16.3517.67 for MELD 26‐30;39.26 43.2147.55 for MELD 31‐34;120.04 128.25137.02 for MELD 35‐40). As a result, candidates with the highest MELD gained the most life years after LT: 0.2, 1.5, 3.5, 5.8, 6.9, 7.2 years for MELD 11‐15, 16‐20, 21‐25, 26‐30, 31‐34, 35‐40, respectively. Therefore, prioritizing candidates by MELD remains a simple, effective strategy for prioritizing candidates with a higher transplant survival benefit over those with lower survival benefit. Abstract : The Model for End‐Stage Liver Disease (MELD) functions not only as a predictor of waitlist mortality, but also as a measure of survival benefit after liver transplantation, and therefore our current allocation policy considers both equity and utility.